KETERLIBATAN KERJA SEBAGAI PEMEDIASI PENGARUH KEPRIBADIAN PROAKTIF DAN PERSEPSI DUKUNGAN ORGANISASIONAL TERHADAP KEPUASAN KERJA - Aurilia Triani Aryaningtyas; Lieli Suharti (Jurnal Manajemen dan Wirausaha, 2013)
This study examined proactive personality effect and perceived organizational support on job satisfaction with job involvement as a mediator variable, using data 200 employees. The results showed proactive personality and perceived organizational support in a positive and significant effect on job satisfaction through job involvement. Theoretical implications supported the theory and existing researches. Manajerial implications suggested the organization to consider proactive personality and perceptions of organizational support as a important factor to encourage more employees involved in work that can improve job satisfaction.